2012
DOI: 10.2747/1548-1603.49.5.735
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Statistical Analyses of Global Trends of Ultraviolet B Fluxes in the Continental United States

Abstract: Abstract. Many environmental factors, such as stratospheric ozone, aerosols, and clouds, may affect ultraviolet (UV) irradiance. The aim of this study is to investigate the possible association between ultraviolet B (UVB) radiation and total cloud amount, ozone, and aerosols simultaneously, leading to the assessment of possible impacts of climate change on UVB flux variations in the continental United States (U.S.). Spatiotemporal correlation analyses were conducted, based on data collected from the Total Ozon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Thus, a dynamic model involving evolutions of interactions on different interfaces is needed to study the separation mechanism of a gas-driven separation device, which has not been well-established yet. In this work, a separation device that consists of a gas-driven actuator, a bolt, three split nuts, and other components is going to be studied [35][36][37]. In the separation process, high-pressure gas is released to overcome friction between a ring and nuts.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a dynamic model involving evolutions of interactions on different interfaces is needed to study the separation mechanism of a gas-driven separation device, which has not been well-established yet. In this work, a separation device that consists of a gas-driven actuator, a bolt, three split nuts, and other components is going to be studied [35][36][37]. In the separation process, high-pressure gas is released to overcome friction between a ring and nuts.…”
Section: Introductionmentioning
confidence: 99%
“…Their major emissions sources are combustion processes, including those from industrial/vehicular/biomass/biofuel, and found in higher abundances around highly populated areas (Lamsal et al 2013 ). Atmospheric ozone, a useful stratospheric gas for absorbing harmful UV radiation (Madronich 1993 ; Gao et al 2012 ), is a greenhouse gas (Fishman et al 1979 ) and a secondary air pollutant in the troposphere (Desqueyroux et al 2002 ; Kim et al 2013 ). Apart from photochemical production, ozone concentrations are also altered via meteorology and dynamics, including downward transport of ozone-rich air from the stratosphere (Holton et al 1995 ; Park et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 In recent years the level of UV-B reaching Earth's surface has increased because the protective stratospheric ozone layer has been eroded by man-made chemicals, such as chlorofluorocarbons and methyl bromide. 2 Although the rapid decline in ozone concentration is now showing improvement, the US Department of Agriculture (USDA) remains concerned about possible harmful effects of increased UV-B on plants and ecosystems. UV-B levels, however, are not typically monitored at weather stations in the United States.…”
mentioning
confidence: 99%